2017
DOI: 10.1080/09583157.2017.1334257
|View full text |Cite
|
Sign up to set email alerts
|

Development of formulations based onStreptomyces rocheistrain PTL2 spores for biocontrol ofRhizoctonia solanidamping-off of tomato seedlings

Abstract: Rhizoctonia solani is one of the most problematic soil-borne pathogenic fungi for several crop cultures worldwide. This study highlights the effectiveness of high-antagonistic Streptomyces rochei strain PTL2, isolated from root tissues of Panicum turgidum, in controlling the R. solani damping-off and growth promotion of tomato (cv. Marmande) seedlings. The isolate PTL2 was characterised for in vitro biocontrol and plant growth-promoting traits. It exhibited remarkable positive results in all trials, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 39 publications
(62 reference statements)
0
30
0
Order By: Relevance
“…Several studies have already reported that antagonist Streptomyces species can be considered as active against numerous phytopathogenic fungi, such as F. oxysporum f. sp. radicis-lycopersici, F. culmorum and R. solani (Yekkour et al, 2012;Zamoum et al, 2017), and have suggested their use as biocontrol agents, or their involvement in the in vivo biocontrol of wheat root rot caused by F. culmorum (Toumatia et al, 2015). The study by El-Tarabily, Hardy GES, Sivasithamparam, Hussein, and Kurtboöke (1997) was the first to provide evidence of the utility of Streptosporangium albidum in the biocontrol of Pythium coloratum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have already reported that antagonist Streptomyces species can be considered as active against numerous phytopathogenic fungi, such as F. oxysporum f. sp. radicis-lycopersici, F. culmorum and R. solani (Yekkour et al, 2012;Zamoum et al, 2017), and have suggested their use as biocontrol agents, or their involvement in the in vivo biocontrol of wheat root rot caused by F. culmorum (Toumatia et al, 2015). The study by El-Tarabily, Hardy GES, Sivasithamparam, Hussein, and Kurtboöke (1997) was the first to provide evidence of the utility of Streptosporangium albidum in the biocontrol of Pythium coloratum.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures were incubated at 30°C for 5 days. Chitinolytic activity was estimated by measuring the diameter of the hydrolytic halo surrounding the actinobacterial colonies (Zamoum, Goudjal, Sabaou, Mathieu, & Zitouni, 2017).…”
Section: Chitinolytic Activitymentioning
confidence: 99%
“…A potential biocontrol Streptomyces strain was isolated from the roots of the Saharan native plant P. turgidum (Zamoum et al, 2017), this Streptomyces strain was identified as S. rochei strain PTL2 and showed a number of PGP traits including the production of hydrogen cyanide (HCN), siderophores, ACC deaminase, and phosphate solubilization. Furthermore, this PLT2 strain showed strong antagonistic activity against the soil-borne pathogenic fungus Rhizoctonia solani, revealing the potential use of this desert PGPR as a biocontrol agent, which could help various crop plants against plant pathogens (Zamoum et al, 2017). In addition, Nocardiopsis dassonvillei MB22 with a strong biocontrol activity was isolated from the Saharan soils and showed several PGP traits including the production of IAA, HCN, and phosphate solubilization (Allali et al, 2019).…”
Section: The North African Desertsmentioning
confidence: 99%
“…because of their diverse host spectra and soil-borne existence, fungal phytopathogens are difficult to control ( Lamichhane et al, 2017 ). R. solani is one of the most important and widespread soil-borne phytopathogenic fungi causing yield losses in more than 200 crops around the world ( Sturrock et al, 2015 ) via seedling damping-off and crown rot ( Montealegre et al, 2010 ; Zamoum et al, 2017 ). A. solani can cause serious damage during all stages of plant growth ( Attia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%